Tingkat Kesesuaian Aspek Keselamatan dan Kesehatan Kerja dalam Pemeliharaan Gedung Menggunakan Gondola - Br Sitepu, Lisa Dwianggraini; Sulistiyorini, Desy (Health Safety Environment, 2024)
Background: High-rise building maintenance faces significant accident risks, particularly in gondola operations. Workers at Central Executive Board (DPP) of Party X perform routine building maintenance. Interview results indicate weather and wind conditions as primary work impediments that workers consistently face. This study evaluates Occupational Health and Safety (OHS) implementation at DPP Party X Building in East Jakarta and its importance for height workers Methods: The research employs qualitative methods through observation, in-depth interviews, and documentation. Researchers apply checklist forms to measure compliance percentages based on Minister of Manpower Regulations (Permenaker) Number 9/2016 and Number 8/2020. Four gondola operators at DPP Party X Building Jakarta participated as informants. Result: OHS standard compliance in height work reaches 95%. Compliance includes planning, work procedures, and Personal Protective Equipment (PPE) usage. Interview results show improved safety supervision and PPE usage consistency. Lifting equipment compliance reaches 83%. While PPE usage and equipment maintenance meet standards, equipment testing still requires certified technical personnel involvement. Conclusions: OHS implementation for working at height workers at DPP Party X Building meets field standards. However, equipment maintenance aspects and certified technical inspections need enhancement to ensure operational equipment safety. Management needs to strengthen cooperation with certified third parties and improve Human capacity through certification programs. Regular OHS evaluations are necessary to ensure effectiveness and continuous improvement Keywords: Implementation of K3; Height; Construction